Perception of the damage caused by birds in fruit crops and alternatives of management in the north and central area of the SantaFe province. (FAVE Sección Ciencias Agrarias, 2018)
Fruit crops are affected by birds and other adversities. The aim of this work was to evaluate the perception of the damage caused by birds and the application of management alternatives to avoid that. A census was made to fruits growers in the central and north area of the Santa Fe province. The majority of growers reported that observed damage by birds, mainly in the stage maturation to harvest. Qualitatively, the damage was considered low or insignificant and, quantitatively, less than 5%. The apple was the most affected crop, and peach the least affected. Monk Parakeet and the Thrush were most frequently identified causing damage. Losses were considered inferior to other adversities. The damage management methods mentioned were, lethal control, scaring, agronomic practices, habitat modification and exclusion. Most growers would not be interested to invest resources to reduce damage by birds.
Keywords: monk parakeet; peach; apple; thrush